Effect of Whole-course Nutrition Management on Patients with Esophageal Cancer Undergoing Concurrent Chemoradiotherapy: A Randomized Control Trial (P05-031-19). (13th June 2019) - Qiu, Yanfang; You, Jie; Lv, Quanjun; Yuan, Ling
Abstract: Objectives: Malnutrition is the most common complication of patients with esophageal cancer, and can lead to poor prognosis and death. It has been shown that good nutritional status can help improve patient outcomes and reduce complications. In the absence of specific evidence of the effect of nutrition on patients with esophageal cancer, the purpose of this study was to investigate the effect of total nutrition management on the prognosis and complications of patients with esophageal cancer through a randomized controlled trial. Methods: 96 patients with esophageal cancer concurrent chemoradiation were randomized to observation group (treated by whole-nutrition management from the Nutrition Support Group (NST)) and control group (treated by the general nutritional method) for 6 weeks approximately. Dietary survey, Patient-Generated Subjective Global Assessment (PG-SGA), body measurement, blood index, quality of life survey and psychological condition survey were assessed at baseline and every week/at the end of the study. Complications, the completion rates of therapy, short-term efficacy evaluation as well as clinical outcomes were measured before discharge. Results: A total of 85 subjects completed the study (observation group = 45, control group = 40). There were significantly different in the changes in serum albumin, prealbumin, and total protein between two groups throughout the trial ( P < 0.05). Radioactive esophagitis, skin symptom of the complications, the roles, emotional functions, social functions, and general health status in the quality of life were statistically different before and after the intervention ( P < 0.05). The difference in the change of other indicators was not statistically significant. Conclusions: Whole-course nutrition management can improve the nutritional status of patients with concurrent chemoradiotherapy of esophageal cancer, reduce the severity of radiation esophagitis and radiation skin reactions, improve the quality of life and relieve their depressive symptoms. Funding Sources: Wu Jieping Medical Foundation Special Fund for Clinical Research of 2017.